Fator de crescimento derivado de plaquetas humanas obtido por uma metodologia rápida e de baixo custo - Barbieri, C. M O [UNESP]; Costa, Paulo Inácio da [UNESP] (My University, 2004)
Human platelet-derived growth factor (PDGF) was purified from lysates of clinically outdated human platelets by ionic exchange chromatography in CM-Sepharose. The eluated fraction was submitted to the Immunoblot/Slot Blot assay using anti-PDGF-AA and anti-PDGF-BB polyclonal antibodies and was evaluated as to its biological activity through the test of [H 3]-thymidine incorporation in NIH/3T3 cell line fibroblasts in culture. The Immunoblot/Slot Blot assay using anti-PDGF-AA and anti-PDGF-BB antibodies proved the presence of the PDGF in chromatographic cationic fraction. The comparison of biological activities between fiblobrast stimulation assay using recombinant PDGF-AB and partially purified PDGF was demonstrated in 165.796 and 157.567 cpm, respectively. This result, proved the potent mitogenic effect of partially purified PDGF and consequently their evidence about the wound healing activity.
Human platelet-derived growth factor obtained by means of a fast and inexpensive methodology
Keywords: PDGF; Platelets; Wound healing; cation; platelet derived growth factor; platelet derived growth factor AA; platelet derived growth factor AB; platelet derived growth factor BB; polyclonal antibody; recombinant platelet derived growth factor; sepharose; thymidine; tritium; wound healing promoting agent; animal cell; cell lysate; cell stimulation; cell strain 3T3; controlled study; drug activity; drug cost; drug potency; drug purification; drug screening; fibroblast culture; immunoblotting; ion exchange chromatography; methodology; mitogenesis; mouse; nonhuman; slot blot hybridization; thrombocyte; wound healing